The spread of covid-19 and psychiatric impact on indigenous peoples - Oliveira, Tainã Brito Siebra de; Moreira, Jorge Lucas de Sousa; Feitosa, Pedro Walisson Gomes; Lima, Danielly Gonçalves Sombra; Dionízio, Bárbara Silveira; Faculdade de M, Modesto Leite (Avanços em Medicina, 2025)
Background: Information on strategies adopted by Indigenous peoples against COVID-19 is scarce, and history shows that Indigenous peoples in the Amazon region may be particularly affected by the  pandemic.Method: The studies were identified in well-known international journals found in two electronic databases: Scopus and Embase. The data were cross-checked with information from the main international newspapers.Results: Mental disorders in the affective spectrum (unipolar major depression, dysthymia, bipolarity) and anxiety disorders (generalized anxiety disorder, panic attacks, social phobia) also mark the reality of Indigenous psychiatric vulnerability.Conclusions: To mitigate the impact of COVID-19 on Indigenous communities in Brazil, a health service for Indigenous groups, a crisis office, and a monitoring panel were created. In the state of Amazonas, home to more Indigenous people than any other Brazilian state, 95% of the intensive care beds are occupied.  Thus, mental health disparities between Indigenous and non-Indigenous peoples may be related to the underlying economic, social, and political inequities that are legacies of colonization and oppression of Indigenous cultures; the disproportionate rates of mental disorders must be understood in context, not as intrinsic predisposition of Indigenous peoples, but as reflecting persistent inequalities.